Effect of upper premolar extractions on the position of the upper lip - Bokas Jim; Collett Tony (Sciendo, 2023)
It has been suggested that Class II division 1 malocclusions treated with extractions result in detrimental changes in the facial profile. This study investigates changes in the position of the upper lip following upper arch extractions only.